Clinical effect of stereotyped B-cell receptor immunoglobulins in chronic lymphocytic leukaemia: a retrospective multicentre study - Baliakas, Panagiotis; Hadzidimitriou, Anastasia; Sutton, Lesley-Ann; Minga, Eva; Agathangelidis, Andreas; Nichelatti, Michele; Tsanousa, Athina; Scarfò, Lydia; Davis, Zadie; Yan, Xiao-Jie; Shanafelt, Tait; Plevova, Karla; et al. (The Lancet. Haematology, 2014)
BACKGROUND: About 30% of cases of chronic lymphocytic leukaemia (CLL) carry quasi-identical B-cell receptor immunoglobulins and can be assigned to distinct stereotyped subsets. Although preliminary evidence suggests that B-cell receptor immunoglobulin stereotypy is relevant from a clinical viewpoint, this aspect has never been explored in a systematic manner or in a cohort of adequate size that would enable clinical conclusions to be drawn. METHODS: For this retrospective, multicentre study, we analysed 8593 patients with CLL for whom immunogenetic data were available. These patients were followed up in 15 academic institutions throughout Europe (in Czech Republic, Denmark, France, Greece, Italy, Netherlands, Sweden, and the UK) and the USA, and data were collected between June 1, 2012, and June 7, 2013. We retrospectively assessed the clinical implications of CLL B-cell receptor immunoglobulin stereotypy, with a particular focus on 14 major stereotyped subsets comprising cases expressing unmutated (U-CLL) or mutated (M-CLL) immunoglobulin heavy chain variable genes. The primary outcome of our analysis was time to first treatment, defined as the time between diagnosis and date of first treatment. FINDINGS: 2878 patients were assigned to a stereotyped subset, of which 1122 patients belonged to one of 14 major subsets. Stereotyped subsets showed significant differences in terms of age, sex, disease burden at diagnosis, CD38 expression, and cytogenetic aberrations of prognostic significance. Patients within a specific subset generally followed the same clinical course, whereas patients in different stereotyped subsets-despite having the same immunoglobulin heavy variable gene and displaying similar immunoglobulin mutational status-showed substantially different times to first treatment. By integrating B-cell receptor immunoglobulin stereotypy (for subsets 1, 2, and 4) into the well established Döhner cytogenetic prognostic model, we showed these, which collectively account for around 7% of all cases of CLL and represent both U-CLL and M-CLL, constituted separate clinical entities, ranging from very indolent (subset 4) to aggressive disease (subsets 1 and 2). INTERPRETATION: The molecular classification of chronic lymphocytic leukaemia based on B-cell receptor immunoglobulin stereotypy improves the Döhner hierarchical model and refines prognostication beyond immunoglobulin mutational status, with potential implications for clinical decision making, especially within prospective clinical trials. FUNDING: European Union; General Secretariat for Research and Technology of Greece; AIRC; Italian Ministry of Health; AIRC Regional Project with Fondazione CARIPARO and CARIVERONA; Regione Veneto on Chronic Lymphocytic Leukemia; Nordic Cancer Union; Swedish Cancer Society; Swedish Research Council; and National Cancer Institute (NIH).